85Sr uptake by the chick embryonic heart: effect of high doses of isoproterenol - Ostádalová, I; Ostádal, B (Canadian journal of physiology and pharmacology, 1992)
The aim of the present study was to establish whether intraamnial administration of toxic doses of isoproterenol to chick embryos increases cardiac accumulation of strontium, the homologue element of calcium. It has been shown that the ability of embryonic tissues (blood, heart, and liver) to accumulate 85Sr decreases significantly during ontogeny. Administration of isoproterenol to chick embryos did not elevate the concentration of 85Sr in the heart. It seems, therefore, that isoproterenol-induced developmental changes in the chick embryonic myocardium are not necessarily due to intracellular calcium (as measured by 85Sr) overload.
Keywords: radioizotopy stroncia; Heart; isoprenalin; Organ Size; velikost orgánu; myokard; kuřecí embryo; zvířata; Strontium Radioisotopes; Myocardium; Chick Embryo; Isoproterenol; srdce; Animals